Golden Holocaust : Origins of the Cigarette Catastrophe and the Case for Abolition. - Proctor, Robert, 1954- (Berkeley : University of California Press, 2012)
The cigarette is the deadliest artifact in the history of human civilization. It is also one of the most beguiling, thanks to more than a century of manipulation at the hands of tobacco industry chemists. In Golden Holocaust, Robert N. Proctor draws on reams of formerly-secret industry documents to explore how the cigarette came to be the most widely-used drug on the planet, with six trillion sticks sold per year. He paints a harrowing picture of tobacco manufacturers conspiring to block the recognition of tobacco-cancer hazards, even as they ensnare legions of scientists and politicians in a.
Timeline of Global Tobacco Mergers and AcquisitionsTimeline of Tobacco Industry Diversification into Candy, Food, Alcohol, and Other Products; Acknowledgments; Index.
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Tobacco industry -- United States -- History; Tobacco use -- Health aspects; Smoking -- Psychological aspects; Persuasion (Psychology); Government Regulation -- United States -- History; Tobacco Industry -- United States -- History; History, 20th Century -- United States; Persuasive Communication -- United States; Smoking -- adverse effects -- United States; Smoking -- psychology -- United States; Tobacco Industry -- economics -- United States; Tobacco Industry -- economics; History, 20th Century; Persuasive Communication; Smoking -- adverse effects; Smoking -- psychology; Tobacco Industry -- history; Government Regulation -- history; United States; Tabac -- Industrie -- États-Unis -- Histoire; Tabagisme -- Aspect psychologique; Médecine -- Histoire -- 20e siècle.; Communication persuasive; PSYCHOLOGY -- Psychopathology -- Addiction; SELF-HELP -- Substance Abuse & Addictions -- General; MEDICAL -- History; Persuasion (Psychology); Smoking -- Psychological aspects; Tobacco industry; Tobacco use -- Health aspects; United States; History